Nonoccupational Postexposure Human Immunodeficiency Virus Prophylaxis: Acceptance Following Sexual Assault. Issue 1 (January 2016) - Draughon Moret, Jessica E.; Hauda, William E.; Price, Bonnie; Sheridan, Daniel J.
Abstract : Background: Nonoccupational postexposure prophylaxis (nPEP) for HIV following sexual assault may decrease the likelihood of HIV transmission. Objective: The purpose of this exploratory chart review study was to examine factors associated with patients accepting post-sexual assault nPEP at three forensic nurse examiner programs in urban settings. Methods: Forensic nursing charts of patients presenting for acute sexual assault care were reviewed as part of a mixed-methods study. Results: Patients assaulted by more than one or an unknown number of assailants were over 12 times more likely to accept the offer of nPEP (adjusted odds ratio [a OR ] = 12.66, 95% CI [2.77, 57.82]). In cases where no condom was used (a OR = 8.57, 95% CI [1.59, 46.10]) or when any injury to the anus or genitalia was noted (a OR = 4.10, 95% CI [1.57, 10.75]), patients were more likely to accept nPEP. Patients with any injury to the face or head were less likely to initiate nPEP (a OR = 0.32, 95% CI [0.11, 0.97]). Discussion: This study is an important first step in understanding factors associated with nPEP acceptance after sexual assault.